EFEKTIVITAS FLIPBOOK DIGITAL PADA MATERI IPAS DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK DI SMK YAPALIS KRIAN - Siti Aisyah; Mustaji Mustaji (Educational Technology Journal, 2023)
The purpose of this study was to determine the feasibility and effectiveness of digital Flipbook media in increasing student learning motivation in class X TKJ SMK Yapalis Krian Sidoarjo in the 2023/2023 academic year. Development model using 4D (Define, Design, Development and Disseminations) The research method uses development research involving qualitative and quantitative research. For data collection techniques using interviews, questionnaires and tests. Structured interview techniques are used to collect media validation data, material to experts. Questionnaire sheets are addressed to students to determine the level of motivation in learning with Flipbook media. While the test is used to determine the impact of motivation, namely student learning outcomes in the form of pre-test and post-test. For data analysis, the writer uses descriptive analysis, validity and reliability and T test. The results of the research on media and material validation showed 76% and 86%, in the large and small group testing the results were 81% and 84% in the very feasible category. The results of student motivation obtained results of 82% of the overall student average. This shows that the existence of Flipbook media can increase student motivation in learning activities.